Ketupat Processing Traditions in Minangkabau: An Eco-Theological, Health, and Cultural Resilience Study - Azhari Akmal Tarigan; Jufri Naldo; Syahrial Arif Hutagalung; Uswatun Hasanah; Ismail Ismail (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
This study examines the Ketupat tradition, a Minangkabau food wrapped in young coconut leaves, through the lenses of eco-theology, public health, and cultural resilience. Employing a qualitative methodology that integrates in-depth interviews with 25 informants (15 entrepreneurs, 5 cultural leaders, and 5 academics), participatory observation, and textual analysis with data analyzed thematically using NVivo software the research was conducted across key centers of Minangkabau diaspora life in Padang (West Sumatra, Indonesia), Yogyakarta (Indonesia), and Negeri Sembilan (Malaysia). The findings reveal three interrelated dimensions. First, the use of natural leaf wrappers embodies the Islamic eco-theological principle of khalifah fil-ardh (humans as stewards of the earth), expressed through faith-driven ecological awareness among tradition bearers. Second, coconut leaves provide tangible health benefits by eliminating risks of chemical migration from plastic and styrofoam packaging, reinforcing community-based food safety rooted in natural materials. Third, Ketupat-making sustains cultural identity and social cohesion within diaspora communities through intergenerational transmission and collective rituals. Overall, the study argues that traditional food practices grounded in natural materials represent a convergence of ecological wisdom, health protection, and spiritual values, underscoring the importance of integrating local wisdom into sustainable food policies and national food security strategies Keyword: Ketupat ; Ketupat; Minangkabau; eco-theology; traditional food systems; public health; cultural resilience; food packaging